Legal approaches to risk of harm in genetic counseling: perspectives from Quebec and Qatar - Patrinos, Dimitri; Ghaly, Mohammed; Al-Shafai, Mashael; Zawati, Ma’n H. (Frontiers in Genetics, 2023)
Genetic counseling is a fast-growing profession worldwide, with genetic counselors taking on increasingly comprehensive and autonomous roles in the healthcare sector. However, the absence of appropriate legal frameworks could potentially create risks of harm to the public. Legal recognition serves to protect the public from risk of harm by regulating the safe and competent practice of healthcare professionals. Genetic counseling is not legally recognized in most world jurisdictions. Examination of the legal status of genetic counseling in different jurisdictions and whether existing legal mechanisms are adequate to address potential risks of harm is therefore timely. This paper examines the different roles of genetic counselors in the Canadian province of Quebec and the state of Qatar, the authors' respective jurisdictions. It considers the types of harms that may be created where appropriate legal mechanisms are lacking, considering the socio-political and legal differences between the two jurisdictions. Moreover, it examines the legal status of genetic counseling in Quebec and Qatar to determine whether these statuses appropriately address the identified risks of harm. The authors argue that existing legal frameworks are inadequate to address these risks and recommend that additional regulatory mechanisms be implemented to properly protect the public from risks of harm.